Trabalho e autonomia do enfermeiro em pronto-socorro adulto: uma abordagem ergológica - Bonfada, Mônica Strapazzon (2019)
The emergency room is considered a gateway to the care of people in emergency and emergency situations, and present the purpose of recovery and maintenance of the patient's health. The nurse in the emergency room is a key professional in the provision of quality care, since care is unpredictable due to the severity and complexity of the cases. The present study had as objective to know how occurs the exercise of the autonomy by nurses work in the emergency room from the point of view of ergology. It is characterized as a qualitative study, of the case study type, with a data triangulation strategy. The research was carried out in a unit of a University Hospital in the south of Brazil, from February to June, 2018. The research population was the nurses of this scenario who worked directly in the care and the nurses of the Internal Nucleus of Regulation. For data collection, systematic non-participant observation, documentary research and semi-structured interview were used, and 23 nurses were interviewed. The analysis of the data was performed through the thematic analysis proposed by Minayo, anchored in the theoretical reference of ergology. . The results obtained in the present are organized into five categories. The first one relates to the contextualization of the emergency room, which reports the complexity, high flow of care and organization of the work of the professionals. In the second category, the relation between the use of self in the managerial and nursing work of the nurse, especially in the organization of the environment, in the assistance of intercurrences and definition of care priorities, as well as in the conduction of the activities of each shift, communication and in working with the team. In the third category, the prescribed work, represented by the standard operating procedures, protocols, norms and routines of the emergency room was observed, as well as the actual work characterized by the need for changes in existing norms at work. In the fourth category, there are described the dramatic use of self and the renormatizations of the work in the emergency room, highlighting the strategies and actions used by the professional nurses in their work, the agility and speed in the attendance of emergencies and emergencies, the need for knowledge to make decisions, and the adverse situations found that result in changes in care protocols according to the need of the clinical situation. It is noteworthy, in this category, that the dramatic of self-use and the renormatizations are influenced by the lack of structure and high demand of care. The fifth category deals with the autonomy of the nurse professional, who is linked to having knowledge, skills and experience, making quick decisions and having responsibilities. They stand out as aspects that facilitate the exercise of autonomy in the work: the good communication and relationship with the multiprofessional team, the knowledge, the experience, the relation with the chiefs and with the nursing technicians. Among the aspects that make autonomy difficult, there is a lack of participation of decisions taken by managers, excessive bureaucracy, lack of human and physical resources, overcrowding, lack of knowledge of nurses in relation to emergency and emergency work, the doctors and the heads. It is concluded that nurses work is constituted from the dynamics of the emergency room, sometimes presenting with limitation, resulting from organizational context and high patient demand. It has autonomy in its work, being recognized by the development of its activities with agility and speed in the making of decisions. The knowledge, experience and values of each professional strengthens their autonomy.